Déjà vu phenomenon as symptom of temporal lobe epilepsy in eight-year-old girl: A case report - Goran Popović; Ranka Mirković; Dejan Bokonjić; Biljana Milinković; Tatjana Elez-Gavrilović (Биомедицинска истраживања, 2020)
Introduction: Deja vu (franc. Déjà vu) is a phenomenon experienced by two thirds of all people. However, this phenomenon can follow aura during the temporal lobe epilepsy. It is believed that it originates from hippocampus, which plays a major role in generating epileptic discharges. Some authors emphasize that in these patients déjà vu phenomenon is not an aura but rather it sometimes refers to the attack itself. Method: In this case report, an eightyear-old girl suffering from repeated crisis of consciousness is described. Case report. The aim of the study was to present the case of an eightyearold girl who underwent three crisis of consciousness, headache behind the forehead as well as the repeated déjà vu phenomenon. The girl was hospitalized, after which medical history was taken and physical examination, as well as other diagnostic tests, were performed. EEG recording revealed an increased electrocortical epileptic activity above the right frontotemporal region. An antiepileptic therapy (Karbapin) leading to attack control was introduced. Conclusion: It is necessary to give temporal lobe epilepsy in children with déjà vu phenomenon serious consideration.
Keywords: crisis of consciousness; déjà vu; child; epilepsy; EEG